Credit Restructuring During the Covid-19 Pandemic : Is it Consistent with Predictions ? - Agung Anggoro Seto; Deny Susanto; Miftahorrozi Miftahorrozi; Tienni Mariana Simanjorang; Irwan Moridu; Nurcahya Hartaty Posumah (Enrichment : Journal of Management, 2022)
Restructuring credit is one of the government's measures to anticipate the impact of the COVID-19 pandemic on the banking industry. This study aimed to determine whether the implementation of credit restructuring meets the predicted expectations. This research was a comparative type. This study employed three variables; Non-Performing Financing (NPF), Financial Deposit Ratio (FDR), and Capital Adequacy Ratio (CAR). The data was utilised quantitative, and the source was secondary information in the form of financial statements. The data was collected using documentation and literature review methods. This study's population consisted of all Islamic commercial banks in Indonesia, comprising 15 banks. The sampling technique employed purposive sampling with a total sample of 10 Islamic commercial banks. The findings revealed that the NPF and CAR values differed before and after credit restructuring. Meanwhile, FDR discovered the inverse outcome, with no difference in FDR before and after credit restructuring. The research result demonstrated that the credit restructuring that has been taking place throughout the COVID-19 pandemic had matched the predicted expectations, with the NFP of Islamic commercial banks decreasing and CAR increasing. On the other hand, credit restructuring has not been able to give a positive boost and can only stabilise the FDR of Islamic commercial banks in Indonesia.